The Role of Learning Environment in Developing Student Character: A Review - Darmawan, Indra; Ridwan, Achmad; Riyadi (CENTRAL ASIA AND THE CAUCASUS, 2022)
The main purpose of this study is to systematically discuss and review the results of previous research related to character development by the learning environment. Four (4) stages of work, namely identification, screening, , eligibility, and including carried out systematically are the methods of this research. Search articles using databases: Elsivier, Taylor, and Wiley during these past six years (2014-2020). International proceedings and English-language journals which are accessed in full text, are a must in collecting articles in this research. The result of study found that 650 research articles have discussed the learning environment and student character. The results of the final study after being screening by the PRISMA method and inclusion criteria found that as many as 15 research articles discussed the learning environment in student personality development. Teachers play an important role in architecture. Good relations with students, able to guide, motivate and provide relevant courses, students.